Effects of replacing corn with triticale in diets for nursery and finishing pigs - Monge, C.R.; Gugle, Terry L.; Feoli, C.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments were conducted to determine the effects of replacing corn (none, 1/3, 2/3, and all) with triticale on growth performance and nutrient digestibility in pigs. For the 34-d nursery experiment, 168 weanling pigs (avg initial weight of 14.8 lb and avg initial age of 21 d) were used. On d 24, fecal samples were collected to allow determination of nutrient digestibility. Overall, pigs consuming diets with 1/3 of the corn replaced with triticale improved ADG (cubic effect, P<0.08) and F/G (linear effect, P<0.01). Digestibility of DM, N, and GE were not affected (P>0.18). For the finishing experiment, 184 pigs (avg initial weight of 131 lb) were used, and fecal samples were collected on d 46. Overall, ADG (linear effect, P<0.02) and ADFI (linear effect, P<0.06) were decreased by 6% as replacement of corn with triticale was increased from none to 100%. But F/G and digestibility of nutrients were not affected (P>0.16), and the negative effects on ADG and ADFI were evident only at 2/3 replacement and replacement of all corn with triticale. In conclusion, replacing corn with triticale improved growth performance in nursery pigs, but reduced ADFI and, thus, ADG in finishing pigs, when more than 1/3 of the corn was replaced.
Keywords: Triticale; Nursery pigs; Finishing pigs; Swine